“This Forcèd League”: The Compassionate Body in The Rape of Lucrece - Huth, Kimberly (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
Two models of compassion coexisted in early modern English thinking: one characterized fellow-feeling as a form of contagion that physically compelled the sharing of passions through the humoral body; the other saw compassion as a moral exercise that required deliberate encouragement and active practice. This paper argues that Shakespeare’s The Rape of Lucrece demonstrates the dynamic interaction of these two models, situating Lucrece’s post-rape failures of productive compassionate interaction as the consequence of the changes produced in her body by the force of Tarquin’s passion, imparted to her through the event of the rape. By tracing Shakespeare’s poetic anatomy of the compassionate body through the rhetoric of opposition in the poem, this analysis elucidates how the construction of gender in humoral theory shapes the narration of the rape and exhibits the enduring influence of the humoral body on the period’s understanding of social life.